El factor religioso en Bulgaria y Rumanía, nuevos miembros de la Unión Europea - Santos, José Luis (UNISCI Discussion Papers, 2007)
This study, made on the basis of the projection of the religious phenomenon in the constitution and the main legislative norms, and also considering their actual realization in the society, tries to assess somehow the degree of historical and current significance of the religious factor in the peoples’ social projection, as well as appreciating the attention paid by the public administration – with modernizing aims and among different political and ideological trends – to the religious factor, as long as it can benefit and not damage the citizens’ good. The conclusion locates Bulgaria and Romania’s state systems within the rest of the European countries.